2009
DOI: 10.1093/bja/aep046
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the bedside central venous catheter placement techniques: landmark vs electrocardiogram guidance

Abstract: During central venous catheterization via the right IJV, landmark guidance was comparable with ECG guidance with regard to CVC tip positioning in the superior vena cava.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 19 publications
1
47
1
1
Order By: Relevance
“…[3161718] CXR on the other hand is less accurate (parallax error is greater and more variable in a portable CXR - anteroposterior view) but offer a cheap and least sophisticated imaging technique to assess a CVC tip in relation to the carina, which is well accepted as a bedside reliable and cost-effective tool. [111819] These two techniques are feasible in all major hospitals. Ultrasound-guided venous puncture and fluoroscopy/C-arm-guided CVC tip placement showed a technical success rate of 98%,[20] but they are not feasible for all major hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…[3161718] CXR on the other hand is less accurate (parallax error is greater and more variable in a portable CXR - anteroposterior view) but offer a cheap and least sophisticated imaging technique to assess a CVC tip in relation to the carina, which is well accepted as a bedside reliable and cost-effective tool. [111819] These two techniques are feasible in all major hospitals. Ultrasound-guided venous puncture and fluoroscopy/C-arm-guided CVC tip placement showed a technical success rate of 98%,[20] but they are not feasible for all major hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…The use of anatomic landmarks is not a sufficiently reliable method for preventing misplacement of a CVC [54,55]. In patients with sinus rhythm, the use of endocavitary EKG during catheter insertion has been shown to predict the correct placement of CVCs inserted via the right internal jugular or right subclavian vein.…”
Section: Diagnosing Complications Of Central Venous Catheterizationmentioning
confidence: 99%
“…(4) In a prospective randomized study by Ezri T et al on 100 patients, for the comparison of CVC insertion by topographic landmark technique and predetermined length (15 cm) insertion, 98% of patients in landmark technique were found to have catheter tip positioned at right place on chest Xray. In this the author did not use TEE to check the position of catheter tip as in our study (5) Lee JH et al compared the accuracy of CVC tip localization between ECG-and landmark-guided catheterization and concluded that central venous catheterization via the right IJV, landmark guidance was comparable with ECG guidance with regard to CVC tip positioning in the superior vena cava (6) In a study by Myung-Chun Kim et al to determine whether the topographical measurement along the course of the central veins can estimate the approximate insertion depths of central venous catheters (CVC). The CVC locations could be predicted with a margin of error between 2.2 cm below the carina and 2.3 cm above the carina in 95% of patients (7) The above studies have done the IJV cannulation using different landmark techniques.…”
Section: Resultsmentioning
confidence: 83%